Porous structured cellulose microsphere acts as biosensor for glucose detection with “signal-and-color” output - Li, Wei; Zhang, Li; Li, Qi; Wang, Shenggao; Luo, Xiaogang; Deng, Hongbing; Liu, Shilin (Carbohydrate polymers, 2019)
•GOx was introduced into spider webs structured cellulose microgel.•The mocrogels had colorimetric responsivity to glucose.•The dual-color glucose probe provided an alternative color choice. In order to develop a biosensor based on porous structured cellulose microspheres for glucose detection with “signal-and-color” output, in this work, active group carboxyl was introduced to cellulose matrix by using plasma technology, and then glucose oxidase (GOx) was chemically immobilized through EDC-NHS cross-linking reaction. The cellulose microgels containing 21.28 mg/g of enzymes exhibited a fast response to 0.003 M glucose within only 4 min. As for detecting subject with a lower concentration of glucose, the probe still worked. When the concentration of glucose solution was 0.005 M, it took only 2 min that the reaction mixture changed from colorless to yellow. By the introduction of starch, the reaction mixture presented as amaranth color. Besides, the porous-structured substrate and the facile plasma technology were also promising for constructing enzyme-driven catalytic systems with enhanced performance.